2014
DOI: 10.1089/neu.2013.3135
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Efficacy of a Proneurogenic Compound after Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is characterized by histopathological damage and long-term sensorimotor and cognitive dysfunction. Recent studies have reported the discovery of the P7C3 class of aminopropyl carbazole agents with potent neuroprotective properties for both newborn neural precursor cells in the adult hippocampus and mature neurons in other regions of the central nervous system. This study tested, for the first time, whether the highly active P7C3-A20 compound would be neuroprotective, promote hippoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
77
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 54 publications
3
77
0
1
Order By: Relevance
“…10,11 Animals were maintained for at least 7 days before the experiment in a temperature-regulated room (23-25°C) on a 12 h light/dark cycle. The rats were fasted, but allowed free access to water overnight before the procedure.…”
Section: Tbi Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Animals were maintained for at least 7 days before the experiment in a temperature-regulated room (23-25°C) on a 12 h light/dark cycle. The rats were fasted, but allowed free access to water overnight before the procedure.…”
Section: Tbi Modelmentioning
confidence: 99%
“…11,15 To confirm tissue damage after TBI, the vibratome brain sections from sham-operated control rats and rats subjected to 2.0 atm FPI followed by 1, 3, 5, and 15 days of recovery were histologically stained and examined by light microscopy. Brain damage was not seen in sham-operated control sections, and observed in the cortical contusion area and CA3 of the hippocampus in all post-TBI brain sections examined (data not shown, but see Fig.…”
Section: Histopathologymentioning
confidence: 99%
“…The functional consequences of decreased cortical injury in MacGreen mice were not investigated in this study however studies investigating cortical protection in traumatic brain injury have demonstrated reduced deficits in sensorimotor tasks such as tactile adhesive removal and locomotor placement tests (Goffus AM et al, 2010, Blaya MO et al, 2013.…”
Section: Discussionmentioning
confidence: 99%
“…levels in the brain. To address this problem, we turned to the neuroprotective aminopropyl carbazole compound P7C3-A20, a small molecule that blocks neuronal cell death, [22][23][24][25][26][27][28] thereby increasing the magnitude of hippocampal neurogenesis. [29][30][31] Treatment of forebrain Ca v 1.2 cKO mice with P7C3-A20 restored normal survival of young hippocampal neurons (Fig.…”
mentioning
confidence: 99%
“…Indeed, the progressive nature of many forms of neuropsychiatric disease, including those linked to CACNA1C, is consistent with neurodegenerative processes that would be amenable to treatment with neuroprotective agents. 46 In this light, it is useful to note that P7C3 compounds have demonstrated protective efficacy in preclinical models of Parkinson disease, 24,[28][29] cognitive decline with aging, 31 amyotrophic lateral sclerosis, 23 traumatic brain injury, [25][26][27] peripheral nerve injury, 22 neurodegeneration-associated depression, 46 and now cell death associated with genetic susceptibility to mental illness. 17 It has recently been reported that P7C3 compounds enhance flux of the nicotinamide adenine dinucleotide (NAD) salvage pathway in normal mammalian cells, and also facilitate NAD recovery following doxorubicin exposure.…”
mentioning
confidence: 99%